Validity and Reliability of the Scale Problematic Smartphone Use (PSU) - Novi Hidayat; Neulis Dewi Julaeha Daswilah (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to examine the validity and reliability of the Smartphone Addiction Scale – Short Version (SAS-SV) among teachers in Vocational High Schools in Bekasi Regency. The research uses a cross-sectional design with a sample of 132 teachers, selected through multistage random sampling. Content validity was tested via expert judgment, construct validity was assessed through Confirmatory Factor Analysis (CFA), and reliability was tested using Cronbach’s Alpha. The findings indicate that SAS-SV has excellent validity and reliability, with a Cronbach’s Alpha value of 0.923. This instrument proved consistent in measuring the construct of Problematic Smartphone Use (PSU) among Vocational High Schools teachers, making it relevant for future studies. This finding contributes significantly to the development of PSU instruments for educators and provides a foundation for policies related to smartphone usage in schools, as well as digital literacy programs and psychological support for teachers. Future studies are recommended using a longitudinal design to expand generalizability and understanding of PSU stability